Analysis of Teachers' Problems in the Implementation of the Independent Curriculum at MI Darul Ulum Jelakcatur - Zumaroh Zumaroh; Khoirotun Nikmah; Retno Nuzilatus Shoimah (AJER: Advanced Journal of Education and Religion, 2024)
The Independent Curriculum has been implemented at MI Darul Ulum Jelakcatur since 2022/2023 in stages. In its implementation, it is inseparable from the problems of planning, implementation and assessment in learning. Therefore, this study aims to: 1) Determine the problems of teachers in the implementation of the Independent Curriculum at MI Darul Ulum Jelakcatur, 2) Determine the factors that cause teachers to experience obstacles in the implementation of the independent curriculum at MI Darul Ulum Jelakcatur, 3) Determine the efforts made by teachers to overcome problems in the implementation of the independent curriculum at MI Darul Ulum Jelakcatur. This type of research is qualitative research using a descriptive approach. The research subjects in this study are the head of the madrasah, curriculum waka, class I teachers and class II teachers. The collection of research data was carried out by observation, interviews and documentation. The data analysis techniques used in this study are the Miles and Huberman model of data reduction, data presentation and conclusion drawn. The results of the study show that: 1) Teachers' problems in the implementation of the Independent Curriculum include planning, implementation and assessment of learning, 2) The factors that cause teachers to experience obstacles in the implementation of the Independent Curriculum are the lack of teachers' understanding of the Independent Curriculum, not all teachers have participated in the Independent Curriculum training, and limited learning resources for student package books, 3) Efforts made by teachers in overcoming problems in the implementation of the Independent Curriculum is by the way teachers participate in regular meetings with the KKG and participate in training.